Spatial analysis of vicariance: A method for using direct geographical information in historical biogeography - Arias Becerra, Joan Salvador (2011)
Based on Hovenkamp's ideas on historical biogeography, we present a method for analysis of taxon history, spatial analysis of vicariance, which uses observed distributions as data, thus requiring neither predefined areas nor assumptions of hierarchical relations between areas. The method is based on identifying sister nodes with disjunct (allopatric/vicariant) distributions. To do this across the tree, internal nodes are assigned distributions (as the sum of the distributions of the descendant nodes). When distributions are less than ideal, ignoring the distribution of the problematic node(s) when assigning a distribution to their ancestors may allow us to consider additional sister nodes (i.e. those resulting from splits basal to the problematic node) as having disjunct distributions. The optimality criterion seeks to find the best (possibly weighted) compromise between the maximum possible number of disjunct sister nodes and the minimum number of eliminated distributions. The method can also take overlap into account. The methodology presented is implemented in VIP, a computer program available at.